THE HERMENEUTICS OF AL-SYAUKANI: THE GRAVE AND THE BARZAKH IN FATḤ AL-QADĪR - Maryono, Maryono; Ridwan, Muhammad; Yusyama, Asep Yana (ILMU USHULUDDIN, 2024)
This article aims to examine Al-Shawkani's interpretation in Al-Shawkani's hermeneutic theory in Tafsir Fathkhul Qadir eschatological verses as well as the implications of the theory and its application to various categorization models of interpretation studies. Using a qualitative literature methodology, it was found that Al-Shawkani's hermeneutics was applied to verses about the graves and the barzakh. This study produces conclusions. First, al-Shawkānī's hermeneutics is built on the principle of convergence between riwāyah and dirāyah. Viewed from the perspective of triadic structures in hermeneutics, "riwāyah" represents the authority of the author, while "dirāyah" represents the authority of the text. The convergence of riwāyah and dirāyah makes al-Shawkānī's interpretation rely on inclusive, egalitarian, and retrospective literalism. Second, al-Shawkānī applies hermeneutical principles consistently to his interpretation of the graves and the barzakh in the Qur'an. Meanwhile, in terms of the history of hermeneutics, what al-Shawkānī does is not far from the discussions that appear in classical hermeneutics, namely in the form of interpretation theory, philological methods, or linguistic understanding methods.